The development of education politics in the period of the military ditctatorship for brazilian higher education - Cunha, Niágara Vieira Soares; Cunha, Marcel Lima (Revista Hipótese, 2018)
The purpose of this study is to understand the developments of educational policy for Higher Education in Brazil from the period of military dictatorship. The methodology we use bibliographical research. We observe that the military regime was able to impose the subordination of the university to the taylorist tint of capitalism with its logic of hyperproductivity, higher education privatization and investment reduction.